2011
DOI: 10.1074/mcp.m110.006593
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Peptide and Protein Quantitation by Liquid Chromatography-Multiple Reaction Monitoring Mass Spectrometry

Abstract: Liquid chromatography-multiple reaction monitoring mass spectrometry of peptides using stable isotope dilution (SID) provides a powerful tool for targeted protein quantitation. However, the high cost of labeled peptide standards for SID poses an obstacle to multiple reaction monitoring studies. We compared SID to a labeled reference peptide (LRP) method, which uses a single labeled peptide as a reference standard for all measured peptides, and a label-free (LF) approach, in which quantitation is based on analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
140
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 108 publications
(148 citation statements)
references
References 47 publications
6
140
1
1
Order By: Relevance
“…To cope with this issue, we selected an internal standard of similar hydrophobicity to each targeted endogenous peptide, which also has close retention time on the C18 column (29), to correct the variations of its content caused during the LC-MS data acquisition, in particular during sample treatment. Compared with the label-free method, previous studies have shown that the use of even a single labeled peptide as a reference standard allows for the increased precision for measuring all other measured endogenous peptides (30). Consistent with this conclusion, another study also showed that the use of synthetic heavy peptides as analog or isotopically labeled internal standards allows the improvement in precision and accuracy of peptide analysis (21).…”
Section: Ds Peptide Identification Using Targeted Lc-ft-ms/ms Analysisupporting
confidence: 70%
“…To cope with this issue, we selected an internal standard of similar hydrophobicity to each targeted endogenous peptide, which also has close retention time on the C18 column (29), to correct the variations of its content caused during the LC-MS data acquisition, in particular during sample treatment. Compared with the label-free method, previous studies have shown that the use of even a single labeled peptide as a reference standard allows for the increased precision for measuring all other measured endogenous peptides (30). Consistent with this conclusion, another study also showed that the use of synthetic heavy peptides as analog or isotopically labeled internal standards allows the improvement in precision and accuracy of peptide analysis (21).…”
Section: Ds Peptide Identification Using Targeted Lc-ft-ms/ms Analysisupporting
confidence: 70%
“…The LRP method requires only a single labeled reference standard and thus offers the most cost-effective approach to a targeted survey of 90 candidate binding partners. However, the method is potentially subject to ionization suppression and interferences because of the lack of labeled standards for all analytes (29). Thus, our use of SID-PRM analyses of a single peptide for each of 26 candidate ASK1-interacting proteins enabled highly precise quantitation, which was sufficient for estimates of complex stoichiometries.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by 14 targeted MS2 scans at a resolution of 17,500 and with an AGC value of 5e5, a max injection time of 80 msec, a 0.5 m/z isolation window, a fixed first mass of 150 m/z, normalized collision energy of 27, and recorded as profile data. The targeted-MS2 methods were controlled with a timed inclusion list containing the target precursor m/z value, charge, and a 3 min retention time window that was determined from prior analyses of synthetic peptide standards as described (29). Lists of all peptides targeted for PRM analysis are given in supplemental Tables S1-S3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instrument quality control assessment was done as described previously (24). Quantitative analyses were done by the labeled reference peptide (LRP) method we described previously (24) using U-13 C 6 , U-15 N 4 -arginine-labeled alkaline phosphatase (AP) peptide (AAQGDITAPGGA*R), ␤-galactosidase (BG) peptide (APLDNDIGVSEAT*R), and ␤-actin (ACTB) peptide (GYSFTTTAE*R) as the reference standard mixture (New England Peptide, Gardner, MA).…”
Section: Methodsmentioning
confidence: 99%